Temperature and WNK-SPAK/OSR1 Kinases Dynamically Regulate Antiviral Human GFP-MxA Biomolecular Condensates in Oral Cancer Cells - Pravin B. Sehgal; Huijuan Yuan; Susan V. DiSenso-Browne (Cells, 2025)
Phase-separated membraneless biomolecular condensates in the cytoplasm and nucleus are now recognized to play a major role in modulating diverse functions in mammalian cells, and contribute to cancer pathogenesis through dysregulated function of condensates of transcription factors such as STAT3 and fusion oncoproteins. Oral cancer, the sixth most prevalent malignancy worldwide, in the absence of overt causes such as tobacco or alcohol, most frequently occurs in a U-shaped zone (floor of mouth, side of tongue, anterior fauces and retromolar region) reflecting the path of liquid transit through the mouth. The cellular basis for this “high-risk” zone and the biochemical mechanisms used by oral cells to combat repetitive tonicity and temperature stresses are incompletely understood. We had previously observed that at 37 °C, in OECM1 oral carcinoma cells, cytoplasmic condensates of antiviral human GFP-MxA GTPase disassembled within 1–2 min of exposure of cells to saliva-like one-third hypotonicity, and underwent “spontaneous” reassembly in the next 5–7 min. Moreover, hypotonic beverages (water, tea, coffee), investigated at 37 °C, triggered this condensate cycling. In the present studies we investigated whether this process was temperature sensitive, representative of cold vs. warm drinks. We observed a slowing of this cycle at 5 °C, and speeding up at 50 °C. The involvement in this disassembly/reassembly process of WNK-SPAK/OSR1 serine-threonine kinase pathway, best studied for regulation of water and Na, K and Cl influx and efflux in kidney tubule cells, was evaluated by us in oral cells using pathway inhibitors WNK463, WNK-IN-11 and closantel. The pan-WNK inhibitor WNK463 inhibited hypotonicity-driven condensate disassembly, while the SPAK/OSR1 inhibitor closantel markedly slowed reassembly. Unexpectedly, the WNK1-selective inhibitor (WNK-IN-11), triggered a dramatic and rapid (within 1 h) spheroid to fibril transition of GFP-MxA condensates in live cells, but without affecting MxA antiviral function. The new data suggest a novel hypothesis for the anatomic localization of oral cancer in the U-shaped “high-risk” zone in the mouth: dysfunction of biomolecular condensates in oral cells along the beverage transit pathway through the mouth due to repetitive tonicity and temperature stresses that might underlie a prooncogenic progression.